2003
DOI: 10.1021/ie020732v
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Performance Design of a Modified Smith Predictor for Unstable Processes with Time Delay

Abstract: The existence of both right-half-plane poles and time delay makes it difficult to obtain a higher control quality. Recently, a modified Smith predictor for unstable processes with time delay was presented and good performance was obtained. In this paper, the modified Smith predictor is discussed. A modified structure is presented. The new one not only is simple for analysis and design but also avoids the improper element. Instead of introduction of an inner loop, a direct design procedure is given and analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 21 publications
1
72
0
1
Order By: Relevance
“…In the case of derivative filter for ideal form of PID controller in Eq. (20), any recommended filter parameter is not safe, rather than that the design of the derivative filter should be an integral part of PID control. Based upon the profound analysis with examples presented by Visioli [43], it can be concluded that, for a PID controller in series form, it is reasonable to choose a fixed derivative factor N>10.…”
Section: Second-order Plus Dead Time Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of derivative filter for ideal form of PID controller in Eq. (20), any recommended filter parameter is not safe, rather than that the design of the derivative filter should be an integral part of PID control. Based upon the profound analysis with examples presented by Visioli [43], it can be concluded that, for a PID controller in series form, it is reasonable to choose a fixed derivative factor N>10.…”
Section: Second-order Plus Dead Time Processmentioning
confidence: 99%
“…For this reason, some modified IMC methods of two-degreesof-freedom (2DOF) control were developed for controlling unstable processes with time delay, such as those proposed by Lee et al [12], Yang et al [13], Wang and Cai [14], Tan et al [15], Liu et al [16] and Jung et al [17]. In addition, 2DOF control methods based on the Smith-Predictor (SP) were proposed by Majhi and Atherton [18], Kwak et al [19], and Zhange et al [20] to achieve a smooth nominal setpoint response without overshoot for first-order unstable processes with time delay.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the classical SP or the similar internal model control (IMC) scheme can only be used for stable processes with time delay due to the internal stability issue [13]. Modified SP or IMC designs have been proposed in the literature (e.g., [4,5,[14][15][16][17][18]) for application to integrating and unstable processes with time delay. It was demonstrated that the filtered SP (FSP) [4,5], which gives a delay-free output prediction, could be generally used for open-loop stable, integrating and unstable processes with time delay.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some modified IMC methods [10][11][12][13][14] of two-degree-of-freedom (2DOF) control were developed for controlling unstable processes with time delay. Several tuning methods [15][16][17] have been proposed based on the Smith-Predictor (SP) to achieve a smooth nominal set-point response without overshoot for first-order unstable processes with time delay. Both the modified IMC and the modified SP methods have the advantage of a faster nominal set-point response without overshoot for unstable processes.…”
Section: Introductionmentioning
confidence: 99%